Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(A=\frac{a^{\frac{5}{2}}\left(a^{\frac{1}{2}}-a^{\frac{-3}{2}}\right)}{a^{\frac{1}{2}}\left(a^{\frac{-1}{2}}-a^{\frac{3}{2}}\right)}=\frac{a^3-a}{1-a^2}=-a\)
Do đó : \(A=-\left(\pi-3\sqrt{2}\right)=3\sqrt{2}-\pi\)
b) Rút gọn B ta có :
\(B=\left(a^{\frac{1}{3}}+b^{\frac{1}{3}}\right)\left[\left(a^{\frac{1}{3}}\right)^2+\left(b^{\frac{1}{3}}\right)^2\right]=\left(a^{\frac{1}{3}}\right)^3+\left(b^{\frac{1}{3}}\right)^3=a+b\)
Do đó :
\(B=\left(7-\sqrt{2}\right)+\left(\sqrt{2}+3\right)=10\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(A=\log_{5^{-2}}5^{\frac{5}{4}}=-\frac{1}{2}.\frac{5}{4}.\log_55=-\frac{5}{8}\)
b) \(B=9^{\frac{1}{2}\log_22-2\log_{27}3}=3^{\log_32-\frac{3}{4}\log_33}=\frac{2}{3^{\frac{3}{4}}}=\frac{2}{3\sqrt[3]{3}}\)
c) \(C=\log_3\log_29=\log_3\log_22^3=\log_33=1\)
d) Ta có \(D=\log_{\frac{1}{3}}6^2-\log_{\frac{1}{3}}400^{\frac{1}{2}}+\log_{\frac{1}{3}}\left(\sqrt[3]{45}\right)\)
\(=\log_{\frac{1}{3}}36-\log_{\frac{1}{3}}20+\log_{\frac{1}{3}}45\)
\(=\log_{\frac{1}{3}}\frac{36.45}{20}=\log_{3^{-1}}81=-\log_33^4=-4\)
![](https://rs.olm.vn/images/avt/0.png?1311)
I*AB=> SI\(\perp\)AB
SI=\(SI=\frac{AB\sqrt{3}}{2}=\frac{a\sqrt{3}}{2}\)
\(V_{k.chop}=\frac{1}{3}.\frac{a\sqrt{3}}{2}.a^2=\frac{a^3\sqrt{3}}{4}\)
b) Kẻ IK//DM(K\(\in\)AD)
Kẻ KH\(\perp\)DM(H\(\in\)DM)
=> d(I,DM)=d(K,DM0=KH
\(\Delta IAK~\Delta DCM\Rightarrow AK=\frac{1}{2}CM=\frac{a}{6}\)=> KD=5a/6
\(cos\widehat{ADM}=cos\widehat{DMC}=\frac{CM}{DM}=\frac{\frac{a}{3}}{\frac{a\sqrt{10}}{3}}=\frac{1}{\sqrt{10}}\)
=> KH=KDsin\(\widehat{ADM}\)=\(\sqrt{1-\cos\widehat{ADM}^2}=\frac{5a}{6}.\frac{3}{\sqrt{10}}=\frac{a\sqrt{10}}{4}\)
d(S,DM)=\(\sqrt{SI^2+d\left(I,DM\right)^2}=\frac{a\sqrt{22}}{4}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(B=\frac{a^{\frac{1}{4}}-a^{\frac{9}{4}}}{a^{\frac{1}{4}}-a^{\frac{5}{4}}}-\frac{b^{-\frac{1}{2}}-b^{\frac{3}{2}}}{b^{\frac{1}{2}}+b^{-\frac{1}{2}}}=\frac{a^{\frac{1}{4}}\left(1-a^2\right)}{a^{\frac{1}{4}}\left(1-a\right)}-\frac{b^{-\frac{1}{2}}\left(1-b^2\right)}{b^{-\frac{1}{2}}\left(1-b\right)}\)
\(=\left(1+a\right)-\left(1-b\right)=a+b=2013-\sqrt{2}+\sqrt{2}-2015=1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(A=\left[\left(\frac{1}{5}\right)^2\right]^{\frac{-3}{2}}-\left[2^{-3}\right]^{\frac{-2}{3}}=5^3-2^2=121\)
b) \(B=6^2+\left[\left(\frac{1}{5}\right)^{\frac{3}{4}}\right]^{-4}=6^2+5^3=161\)
c) \(C=\frac{a^{\sqrt{5}+3}.a^{\sqrt{5}\left(\sqrt{5}-1\right)}}{\left(a^{2\sqrt{2}-1}\right)^{2\sqrt{2}+1}}=\frac{a^{\sqrt{5}+3}.a^{5-\sqrt{5}}}{a^{\left(2\sqrt{2}\right)^2-1^2}}\)
\(=\frac{a^{\sqrt{5}+3+5-\sqrt{5}}}{a^{8-1}}=\frac{a^8}{a^7}=a\)
d) \(D=\left(a^{\frac{1}{2}}-b^{\frac{1}{2}}\right)^2:\left(b-2b\sqrt{\frac{b}{a}}+\frac{b^2}{a}\right)\)
\(=\left(\sqrt{a}-\sqrt{b}\right)^2:b\left[1-2\sqrt{\frac{b}{a}}+\left(\sqrt{\frac{b}{a}}\right)^2\right]\)
\(=\left(\sqrt{a}-\sqrt{b}\right)^2:b\left(1-\sqrt{b}a\right)^2\)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(F=\left(1-2\sqrt{\frac{a}{b}}+\frac{a}{b}\right):\left(a^{\frac{1}{2}}-b^{\frac{1}{2}}\right)^2=\left(1-\sqrt{\frac{a}{b}}\right)^2:\left(\sqrt{a}-\sqrt{b}\right)^2\)
\(=\frac{\left(\sqrt{b}-\sqrt{a}\right)^2}{b}.\frac{1}{\left(\sqrt{a}-\sqrt{b}\right)^2}=\frac{1}{b}\)
ĐK: \(ab\ge0;b\ne0\)
\(F=\left(1-2\sqrt{\frac{a}{b}}+\frac{a}{b}\right):\left(a^{\frac{1}{2}}-b^{\frac{1}{2}}\right)^2\)
\(=\left(\sqrt{\frac{a}{b}}-1\right)^2:\left(\sqrt{a}-\sqrt{b}\right)^2=\frac{\left(\sqrt{a}-\sqrt{b}\right)^2}{b}.\frac{1}{\left(\sqrt{a}-\sqrt{b}\right)^2}=\frac{1}{b}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a. \(2^{2\log_25+\log_{\frac{1}{2}}9}\) và \(\frac{\sqrt{626}}{6}\)
Ta có : \(2^{2\log_25+\log_{\frac{1}{2}}9}=2^{\log_225-\log_29}=2^{\log_2\frac{25}{9}}=\frac{25}{9}=\frac{\sqrt{625}}{9}< \frac{\sqrt{626}}{6}\)
\(\Rightarrow2^{2\log_25+\log_{\frac{1}{2}}9}< \frac{\sqrt{626}}{6}\)
b. \(3^{\log_61,1}\) và \(7^{\log_60,99}\)
Ta có : \(\begin{cases}\log_61,1>0\Rightarrow3^{\log_61,1}>3^0=1\\\log_60,99< 0\Rightarrow7^{\log_60,99}< 7^0=1\end{cases}\)
\(\Rightarrow3^{\log_61,1}>7^{\log_60,99}\)
c. \(\log_{\frac{1}{3}}\frac{1}{80}\) và \(\log_{\frac{1}{2}}\frac{1}{15+\sqrt{2}}\)
Ta có : \(\begin{cases}\log_{\frac{1}{2}}\frac{1}{80}=\log_{3^{-1}}80^{-1}=\log_380< \log_381=4\\\log_{\frac{1}{2}}\frac{1}{15+\sqrt{2}}=\log_{2^{-1}}\left(15+\sqrt{2}\right)^{-1}=\log_2\left(15+\sqrt{2}\right)>\log_216=4\end{cases}\)
\(\Rightarrow\log_{\frac{1}{3}}\frac{1}{80}< \log_{\frac{1}{2}}\frac{1}{15+\sqrt{2}}\)